Cyclization via Metal-Catalyzed Hydrogen Atom Transfer/Radical-Polar Crossover - Shigehisa, Hiroki (Synlett, 2024)
Catalytic transformations of alkenes via the metal-hydride hydrogen atom transfer (MHAT) mechanism have notably advanced synthetic organic chemistry. This Account focuses on MHAT/radical-polar crossover (MHAT/RPC) conditions, offering a novel perspective on generating electrophilic intermediates and facilitating various intramolecular reactions. On using cobalt hydrides, the MHAT mechanism displays exceptional chemoselectivity and functional group tolerance, making it invaluable for the construction of complex biologically relevant molecules under mild conditions. Recent developments have enhanced regioselectivity and expanded the scope of MHAT-type reactions, enabling the formation of cyclic molecules via hydroalkoxylation, hydroacyloxylation, and hydroamination. Notably, the addition of an oxidant to traditional MHAT systems enables the synthesis of rare cationic alkylcobalt(IV) complexes, bridging radical mechanisms to ionic reaction systems. This Account culminates with examples of natural product syntheses and an exploration of asymmetric intramolecular hydroalkoxylations, highlighting the ongoing challenges and opportunities for future research to achieve higher enantioselectivity. This comprehensive study revisits the historical evolution of the MHAT mechanism and provides a groundwork for further innovations on the synthesis of structurally diverse and complex natural products.1 Introduction2 Intramolecular Hydroalkoxylation and Hydroacyloxylation Reactions3 Intramolecular Hydroamination Reactions4 Intramolecular Hydroarylation Reactions5 Deprotective Cyclization6 Asymmetric Intramolecular Hydroalkoxylation7 Conclusion
Keywords: cyclization; cobalt; metal-hydride; radical-polar crossover; alkenes